Pengadaan Sarana Penunjang Kegiatan Pelestarian Sumberdaya Alam Kawasan Hutan Gunung Tilu di Desa Cimara Kecamatan Cibeureum, Kuningan Jawa Barat - Adhya, Ilham; Hendrayana, Yayan; Supartono, Toto; Herlina, Nina; Nasihin, Iing; Nurdin, Nurdin; Waniatri, Wina; Nurlaila, Ai; Fujiman, Heris; Syahban, Fahrul Shobarudin; Althaaf, Naufal (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2023)
Preserving natural resources besides requiring the collaboration of all parties in its implementation, also requires supporting facilities and infrastructure, one of the efforts to preserve forest resources in the Mount Tilu forest area requires the existence of a meeting hall that can be used by all people who are active around Mount Tilu. Saung Kehati is a collaboration of the local community and the Faculty of Forestry, University of Kuningan. The presence of Saung Kehati is expected to be a means of supporting the preservation of Mount Tilu's natural resources. The implementation method uses the observation approach to the need for supporting facilities for forest resource conservation activities and facilitation of facilities and socialization regarding the use of meeting halls/saung/shelters. The target of this community service is the people of Cimara Village. The activity location is located on community-owned land bordering the Mount Tilu Forest area and the Tilu Mountain Forest area. The community service activities carried out in Cimara Village, Cibeureum District, Kuningan Regency ran smoothly and the participation of the community in participating in these activities was quite high, the existence of Saung Kehati increased activities related to the preservation of natural resources in the Mount Tilu forest area. Pelestarian sumberdaya alam disamping memerlukan kolaborasi semua pihak dalam pelaksanaannya, juga memerlukan sarana dan prasarana penunjang, salah satu upaya pelestarian sumberdaya hutan pada kawasan hutan Gunung Tilu memerlukan adanya balai sarana pertemuan yang dapat digunakan oleh seluruh masyarakat yang beraktivitas di sekitar Gunung Tilu. Saung Kehati ini merupakan kolaborasi dari masyarakat setempat dan Fakultas Kehutanan Universitas Kuningan. Kehadiran Saung Kehati diharapkan menjadi sarana pendukung pelestarian sumberdaya alam Gunung Tilu. Metode pelaksanaan dengan pendekatan observasi kebutuhan sarana penunjang kegiatan pelestarian sumberdaya hutan dan fasilitasi sarana serta sosialisasi mengenai pemanfaatan balai pertemuan/saung/shelter. Sasaran pengabdian kepada masyarakat ini adalah masyarakat Desa Cimara. Lokasi kegiatan terletak di lahan milik masyarakat yang berbatasan dengan kawasan Hutan Gunung Tilu dan kawasan Hutan Gunung Tilu. Kegiatan pengabdian kepada masyarakat yang dilakukan di Desa Cimara Kecamatan Cibeureum Kabupaten Kuningan berjalan dengan lancar dan peran serta masyarakat dalam mengikuti kegiatan tersebut cukup tinggi, keberadaan Saung Kehati meningkatkan aktivitas yang berkaitan dengan pelestarian sumberdaya alam kawasan hutan Gunung Tilu.